2022
DOI: 10.1002/slct.202201574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NaY Zeolite at Different Calcination Temperatures on the Activity in Hydroformylation of Formaldehyde

Abstract: The NaY zeolites were prepared by hydrothermal synthesis method. The influence of NaY zeolite calcined at different temperatures as carriers for Rh/NaY catalysts on the hydroformylation of formaldehyde was investigated. The physical and chemical properties of Rh/NaY catalysts and their performance were characterized in details. When the zeolites were calcined at 400-700 °C, the crystal structure and morphology were kept unchanged within this range of calcination temperature. However, the surface crystallinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The higher pH PZC value might be due to Si–OH and Al–OH on the surface and the inner surface of zeolite, which was partly dissociated into Si–O – , Al–O – , and H + in water and thus decrease the adsorption capacity of acidic H 2 S. When the initial pH value was 2, the equilibrium pH value of both the natural zeolite and calcined zeolite gradually increased with the increasing zeolite content, indicating that the H + adsorption capacity of the calcined zeolite was higher than that of the natural zeolite. This might be due to that the decrease of crystallinity and the increase of lattice defects increased the contents of the large radius cations, such as Na + and Mg 2+ , in the calcined zeolite, which could be replaced by H + …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher pH PZC value might be due to Si–OH and Al–OH on the surface and the inner surface of zeolite, which was partly dissociated into Si–O – , Al–O – , and H + in water and thus decrease the adsorption capacity of acidic H 2 S. When the initial pH value was 2, the equilibrium pH value of both the natural zeolite and calcined zeolite gradually increased with the increasing zeolite content, indicating that the H + adsorption capacity of the calcined zeolite was higher than that of the natural zeolite. This might be due to that the decrease of crystallinity and the increase of lattice defects increased the contents of the large radius cations, such as Na + and Mg 2+ , in the calcined zeolite, which could be replaced by H + …”
Section: Resultsmentioning
confidence: 99%
“…The granular structure of the calcined zeolite was flat, and the surface was relatively scattered and loose, indicating that calcination could broaden the channel of zeolite and remove the adsorbed gases and impurities on the surface of zeolite. Guo et al found that calcination could change a zeolite structure by means such as crystal structure collapse, water removal, phase change, and bond rupture. When the calcination temperature was high, the crystal and surface structure of the zeolite changed significantly and even melted at 800 °C, resulting in a decrease in the active surface area …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we consider elevated temperatures of 750 K, 1000 K and 1250 K. These temperatures are within the range in which spontaneous framework destruction and volatilization of the Pt cluster is avoided, and only extend mildly beyond common catalytic applications or calcination temperature ranges for zeolites. 30,31 We apply these temperatures to enhance sampling of Pt migration, while retaining the underlying physical nature of the system relevant at lower temperatures. Results from 750 K and 1000 K are shown in the ESI, † and reflect the observation that at 1250 K, the same qualitative behaviours are observed, with higher frequency.…”
Section: Migration Of Pt 1 Pt 3 and Pt 5 In Chamentioning
confidence: 99%
“…Preliminary simulations showed that 25 ns simulations at room temperature are insufficient to induce migration events. Therefore, we consider elevated temperatures of 750 K, 1000 K and 1250 K. These temperatures are within the range in which spontaneous framework destruction and volatilization of the Pt cluster is avoided, and only extend mildly beyond common catalytic applications or calcination temperature ranges for zeolites (29,30). We apply these temperatures to enhance sampling of Pt migration, while retaining the underlying physical nature of the system relevant at lower temperatures.…”
mentioning
confidence: 99%